Ethics of Waste: Disposability, Self-cultivation and the Art of Transience - Laboni Banerjee (Utan Kayu Publishing, 2025)
AbstractIn today’s world, waste is perhaps the most significant yet complicated category deprived of a proper definition. For environmentalists, waste as a practice of excess stands for death, whereas for commodity cultures, it represents economic freedom and personal choice. Amid the appeals to save the planet and the tendency to possess and accumulate, the solid interconnections we once had with our waste, have been long forgotten. What we are left with, is a restricted source as the moral motivation for responsible abandonment, reflecting the core of actual crisis. This reality presents substantial obstacles in finding ways to coexist with the waste we’ve neglected every day. The article hence intends to collect nearly everything that modern society throws away and never really looks back. In taking up this as a challenge, I aim to explore how waste, often seen as worthless detritus, contributes to shaping the self and ethical sensibilities. When it comes to waste management, the intention is neither to imply the need for changes, based on fear or disgust nor to alter its apparent negative role into a positive one. Instead, what I do desire is to provide, waste material, the attention it deserves, by considering and re-considering various instances of their crucial generative role.